1975
DOI: 10.1007/bf00422394
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of pancreatic IRI output rate and its relation to glucose tolerance in normal anaesthetized dogs

Abstract: Summary. The pancreaticoduodenal and portal venous blood flows were recorded electromagnetically in anaesthetized dogs. Blood glucose and IRI were measured in the arterial, portal, and peripheral venous as well as in the intestinal venous blood. By a mathematical model the actual net IRI output of the whole pancreas was estimated. Under basal conditions it is 10.2 + 2.4 mU/min (n = 30; 26 kg mean body wt.). After i.v. glucose injection, IRI output is rapidly enhanced. The biphasic nature of this reaction was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Since glucagon and insulin were infused at their normal physiological site and at rates which maintained their plasma concentrations it was possible, by assuming their extraction had not changed, to estimate the secretion rate of each hormone. In the case of insulin, this was about 400 ,U/kg per min, a value in agreement with earlier work (53,54). Recently Fischer et al (54), by using direct A-V difference measurements in the postabsorptive dog, showed that the basal secretion rate of insulin was 392 AU/kg per min.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Since glucagon and insulin were infused at their normal physiological site and at rates which maintained their plasma concentrations it was possible, by assuming their extraction had not changed, to estimate the secretion rate of each hormone. In the case of insulin, this was about 400 ,U/kg per min, a value in agreement with earlier work (53,54). Recently Fischer et al (54), by using direct A-V difference measurements in the postabsorptive dog, showed that the basal secretion rate of insulin was 392 AU/kg per min.…”
Section: Resultssupporting
confidence: 87%
“…In the case of insulin, this was about 400 ,U/kg per min, a value in agreement with earlier work (53,54). Recently Fischer et al (54), by using direct A-V difference measurements in the postabsorptive dog, showed that the basal secretion rate of insulin was 392 AU/kg per min. The basal secretion rate of glucagon, on the other hand, has not been as clearly assessed but it would appear from the present study that it is about 1 ng/kg per min in the postabsorptive state.…”
Section: Resultssupporting
confidence: 87%
“…Comparing our restilts, with the rise in pancreatic blood flow after glucose infusion [1,12], it is observed that both changes are parallel. It may further be noted that the effect of glucose infusion to other organ perfusion rates are not clearly understood at present.…”
Section: Discussionmentioning
confidence: 67%
“…administration of glucose induces a significant increase in pancreatic blood flow [1,12]. This observation suggests that besides the insulinogenic and insulin-secretory effects, glucose may produce some changes secondary to alterations in regional circulation.…”
mentioning
confidence: 98%
“…This factor might well vary, but, corresponding to an average loss of 50% of the insulin reaching the liver via the portal vein [8,16], this factor would be 2.0 for insulin secreted or administered into the splanchnic system. In these experiments, however, F = 1.0 because the insulin was administered peripherally so that there was no primary (hepatic) drain of the whole dose.…”
Section: Discussionmentioning
confidence: 99%